High prevalence and low cure rate of tuberculosis among patients with HIV in Xinjiang, China. Issue 1 (December 2017) - Maimaiti, Rena; Zhang, Yuexin; Pan, Kejun; Mijiti, Peierdun; Wubili, Maimaitiali; Musa, Maimaitijiang; Andersson, Rune
Abstract Background Tuberculosis and HIV co-epidemics are problems in many parts of the world. Xinjiang is a high tuberculosis and HIV prevalence area in China. We aimed to investigate the prevalence and cure rate of tuberculosis among HIV positive patients in Xinjiang. Methods In a retrospective study between 2006 and 2011, clinical and laboratory data on 333 patients with HIV and tuberculosis were compared to 2668 patients with HIV only. There were 31 HIV positive patients with no data on tuberculosis. Results The prevalence of tuberculosis co-infection among the HIV positive patients was 11% (95% CI 10–12%), significantly higher than the national figure in China of 2%. In most cases HIV was diagnosed late, with advanced immunodeficiency. The use of isoniazid preventive therapy was only 57.9% in patients without tuberculosis who fulfilled the criteria for receiving this prevention. The cure rate one year after diagnosis was 69.2%, which was lower than the officially reported 91.4% in all tuberculosis cases in Xinjiang in 2011. The hazard of not surviving over the five years was significantly higher in patients with HIV + tuberculosis compared to HIV only after adjusting for sex and Intravenous drug use with HR = 1.84 (95% CI 1.43-2.35;p < 0.0001). Conclusions The prevalence of tuberculosis among HIV positive patients in Xinjiang was higher than in China taken as a whole, and HIV was diagnosed late, with underuse of isoniazid preventive therapy. The low cure rate and reduced survival can be due to late diagnosis of HIV and no testing for antibiotic resistance, together with insufficient control of adherence to the treatment regimens for tuberculosis and HIV.